Simulation of laser impact welding for dissimilar additively manufactured foils considering influence of inhomogeneous microstructure. (15th January 2021) - Sunny, Sumair; Gleason, Glenn; Mathews, Ritin; Malik, Arif
Abstract: Introduced is a comprehensive numerical modeling framework that includes microstructure when simulating the laser impact welding (LIW) of metals to study the transient phenomena that occur during weld formation. Such transient phenomena include evolution of shear stresses, plastic strains, thermal response, and material jetting. Inhomogeneous microstructures for two dissimilar foils (aluminum 1100 and stainless steel 304) are first predicted using the Dynamic Kinetic Monte Carlo (KMC) method to simulate laser-based powder bed fusion (PBF-LB) additive manufacturing (AM). These microstructures are subsequently incorporated into an Eulerian finite element (FE) simulation of the LIW process, enabling prediction of grain elongations that result from the varying yield surfaces, stacking fault energies, and grain-boundary sliding effects. Trends in the predicted microstructure deformation patterns show strong agreement with those from experimental images in the literature. Compared to existing homogeneous models, the new framework with inhomogeneous AM microstructure reveals higher collision velocities at the weld interface, resulting in increased plastic strain rates, greater plastic heat dissipation, and increased material jetting with higher jet temperatures. The framework allows for new opportunities to study correlations between grain topography (as well as polycrystalline metal texture) and the transient process phenomena occurring at the impact weld interface. Graphical abstract: Unlabelled Image Highlights: Presented is a novel comprehensive modeling framework that captures inhomogeneous microstructure-driven anisotropic effects during simulation of laser impact welding The findings reveal grain elongation and alignment resulting from grain-boundary sliding, which confirms the development of adiabatic shear banding By capturing microstructure, increased plastic strain rates along the weld interface are revealed, resulting in greater plastic heat dissipation Unlike existing homogeneous models, findings with the new framework reveal increased jetting with higher temperatures, even at lower collision velocities